Dilapidation Survey and Report: A Case Study of Sekolah Menengah Pendidikan Khas Vokasional Shah Alam (SMPKVSA) - Yahya, Ahmad Nizamuddin; Shukri, Sharyzee Mohmad; Taib, Idris (MAJ - Malaysia Architectural Journal, 2022)
Dilapidation report and dilapidation survey the two processes done in stages to provide information about existing building structure for further action by its owner or manager. Building surveyor will do their survey to existing structure of a building which this action called dilapidation survey before they could produce official report about the condition of that building which the report name was dilapidation report for further action. This article intended to give an overview on the importance of dilapidation survey and report. The method of this research is focusing on the case study which a dilapidation survey and report done for Sekolah Menengah Pendidikan Khas Vokasional Shah Alam beside literature review about dilapidation survey and report. This article will discuss about a method to do defect inspection on site known as dilapidation survey and a method to produce an official report recording all the defect found known as dilapidation report. Also, a significant of Dilapidation Survey Report in construction industry as well as their role in building conservation. The findings from this exploratory review conclude that the importance of building dilapidation survey and report even it was a tedious and time-consuming process.